PERAN WTO DALAM MEMBANGUN PENEGAKAN HUKUM INTERNASIONAL TERHADAP PROTEKSIONISME (STUDI KASUS: SENGKETA DAGANG ROKOK KRETEK INDONESIA) - Farahdiba Rahma Bachtiar (UIN ALAUDDIN MAKASSAR, 2020)
Indonesia’s objection to the United States (US) over a clove ban in 2010 was one of the most difficult trade dispute cases that Indonesia has ever submitted. The dispute between both countries in the clove cigarettes negotiations was actually completed in 2014 after the two countries agreed on mutual understanding (MoU) related to cigarettes. Indonesia's victory over the Dispute Settlement Body (DSB) by the World Trade Organization (WTO) shows the enforcement of international law in intervening in a country's domestic policies.Although it took great deal of time, Indonesia's victory over US becomes a lesson learned. This victory proves the role of the WTO in resolving trade dispute cases and refutes the notion of a superpower in particular the US being immune to the international law. US domestic trade policies that impose a ban on clove cigarettes have deviated from WTO rules and have harmed Indonesia as a producer